Determinants of the heart rate variability in type 1 diabetes mellitus - Hajdu, Máté; Garmpis, Konstandia; Vértes, Vivien; Vorobcsuk-Varga, Noémi; Molnár, Gergő Attila; Hejjel, László; Wittmann, István; Faludi, Réka (Frontiers in Endocrinology, 2023)
Background: Evaluation of heart rate variability (HRV) detects the early subclinical alterations of the autonomic nervous system. Thus, impaired HRV is the earliest subclinical marker of cardiac autonomic neuropathy (CAN) in type 1 diabetes mellitus (T1DM).We aimed to explore the HRV parameters in asymptomatic T1DM patients and compare them with the results obtained in healthy subjects. Potential associations between HRV parameters and the established risk factors for CAN and cardiovascular diseases were also investigated.Methods: Seventy T1DM patients (38±12 years, 46 female) and 30 healthy subjects were enrolled into the study. For HRV analysis, beat-to-beat heart rate was recorded, for 30 minutes. The less noisy 5minute segment of the recording was analyzed by Bittium Cardiac Navigator HRV analysis software.Time-domain, frequency-domain, and nonlinear indices were calculated.Regarding LF/HF ratio, no differences were found between the two populations (p=0.227).Further time-domain, frequency-domain, and nonlinear HRV indices were significantly lower in T1DM patients (each p <0.001). In multiple linear models, disease duration remained the only independent predictor of LF/HF ratio (p=0.019). HbA1c was found to be significant independent predictor of all further time-domain (SDNN, p<0.001; rMSSD, p<0.001), frequency-domain (VLF, p<0.001; LF, p=0.002; HF, p=0.006; Total Power, p=0.002) and nonlinear indices (SD1, p=0.006; SD2, p=0.007), alone, or in combination with other factors, such as age or body mass index.Conclusions: Asymptomatic T1DM patients have significantly reduced overall HRV as compared with healthy subjects, indicating subclinical CAN. Quality of the glycemic control is important determinant of HRV among T1DM patients. This relationship is independent of other risk factors for CAN or cardiovascular diseases.